2018
DOI: 10.30880/ijie.2018.10.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Effect of Variate Cross-Sectional Profile on Conformal Cooling Channels in Plastic Injection Moulding

Abstract: Cooling system is an important role in designing a productive plastic injection moulding (PIM). The selection of geometry and layout for plastic injection moulding cooling channels strongly influences the cooling performance such as cooling time and thermal distribution that leads to shrinkage and warpage. This paper presents the study to determine the best cooling channel layout and cross-sectional profile which include circular straight drilled cooling channels, circular conformal cooling channels, square sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…When comparing the conformal cooling channels with respect to the geometry of their cross-section, it has been observed that the surface area of the conformal channels is an important parameter in the reduction of the cooling time and the improvement of the quality of the part [ 17 ]. Along these lines, although the circular cross-section is the most common in the design of conformal channels, research has been carried out to develop conformal channels with non-circular cross-sections such as square, rectangular, rhomboid, elliptical, water drop, etc., [ 18 , 19 ]. Several authors have made use of a square section for the cooling channels by making cooling slots in the mold [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the conformal cooling channels with respect to the geometry of their cross-section, it has been observed that the surface area of the conformal channels is an important parameter in the reduction of the cooling time and the improvement of the quality of the part [ 17 ]. Along these lines, although the circular cross-section is the most common in the design of conformal channels, research has been carried out to develop conformal channels with non-circular cross-sections such as square, rectangular, rhomboid, elliptical, water drop, etc., [ 18 , 19 ]. Several authors have made use of a square section for the cooling channels by making cooling slots in the mold [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%